Outer membrane vesicles secreted from Actinobacillus pleuropneumoniae isolate disseminating the floR resistance gene to Enterobacteriaceae - Xu, Minsheng; Ke, Haiyi; Zang, Yingan; Gou, Hongchao; Yang, Dongxia; Shi, Keda; Zhang, Kunli; Li, Yan; Jiang, Zhiyong; Chu, Pinpin; Zhai, Shaolun; Li, Chunling (Frontiers in Microbiology, 2024)
Actinobacillus pleuropneumoniae is an important respiratory pig pathogen that causes substantial losses in the worldwide swine industry. The resistance spectrum of A.pleuropneumoniae is becoming increasingly wider, and multidrug resistance is extremely severe. By facilitating the dissemination of resistance determinants, horizontal gene transfer (HGT) is crucial to the development of the bacterial genome. However, the resistance genes can be transferred horizontally via A.pleuropneumoniaederived outer membrane vesicles (OMVs) remains unreported. In this study, we used Illumina NovaSeq and PacBio SequeI sequencing platforms to determine the whole genome sequence of A.pleuropneumoniae GD2107, a multidrug-resistant isolate from China. We detected a plasmid in the isolate named pGD2107-1; the plasmid was 5,027 bp in size with 7 putative open reading frames (ORF) and included the floR resistance genes. The carriage of resistance genes in A.pleuropneumoniae OMVs was identified using PCR assay, and then we thoroughly evaluated the influence of OMVs on the horizontal transfer of drug-resistant plasmids. The transfer of the plasmid to recipient bacteria via OMVs was confirmed by PCR. In growth competition experiments, all recipients carrying the pGD2107-1 plasmid exhibited a fitness cost compared to the corresponding original recipients. This study revealed that OMVs could mediate interspecific horizontal transfer of the resistance plasmid pGD2107-1 into Escherichia coli recipient strains and significantly enhance the resistance of the transformants. In brief, A.pleuropneumoniae-OMVs are the pivotal role of vectors for dissemination of the floR gene spread and may contribute to more antimicrobial resistance genes transfer in other Enterobacteriaceae.